Biology and reproductive capacity of Spodoptera eridania (Cramer) (Lepidoptera, Noctuidae) in different soybean cultivars - Favetti, Bruna Magda [UNESP]; Butnariu, Alessandra Regina; Foerster, Luis Amilton (Soc Brasileira Entomologia, 2015)
This study aimed to evaluate the development, survival and reproductive capacity of Spodoptera eridania in four soybean cultivars. The experiment was conducted in the laboratory, in a climatic chamber at 25 degrees C +/- C, 70 +/- 10% relative humidity and 12 h photophase. The cultivars used were: FMT Tabarana, BRS/MT Pintado, FMT Tucunare and Monsoy 8757, all conventional cultivars with medium cycles. All cultivars tested allowed the development of S. eridania. However, Monsoy 8757 was the cultivar that most affected the prolonged in the duration larval, pupal and total cycle, showed lower pupal weight as well as reduction in the intrinsic rate increase. These results contribute to the management of this species in regions of outbreaks in soybean areas. (C) 2015 Sociedade Brasileira de Entomologia. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Development; Glycine max; Monsoy 8757; Southern armyworms